PENERAPAN MODEL PEMBELAJARAN ISTIQRA’I UNTUK MENINGKATKAN PEMAHAMAN NAHWU SISWI KELAS VII-A SEMESTER GENAP MTs DARUL HUFFAZH PESAWARAN TAHUN PELAJARAN 2013/2014 M: PENERAPAN MODEL PEMBELAJARAN ISTIQRA’I - Hariri Kurniawan; Muhammad Wisnu Khumaidi; Nurkholis (An Naba, 2019)
This research is conducted based on the difficulty of students in understanding the rules of nahwu that are taught in the class and based on the low grades they got from this subject. This is based on observations that show the low average value of students on Arabic. Based on this background, the researcher is interested in applying the istiqra'i method so that students' understanding of the nahwu rules increases. The formulation of the problem in this study is: Does the application of the istiqra'i learning model can improve the students’ ability in class VII A of MTs Darul Huffaz to understand the rules of nahwu? This research uses Classroom Action Research (CAR). The purpose of this research is to determine the role of the application of the istiqra'i method to the ability of students to understand nahwu rules. The subjects of this research are the 20th grade students of VIIA. This research is conducted in 2 cycles. Based on the results of student evaluation tests in cycle 1 and cycle 2, it can be concluded that the application of the istiqra'i method is quite instrumental in increasing students' understanding of the nahwu rules because the acquisition of the average value of all aspects of the understanding of nahwu taught has increased. The average value of the test results of all aspects of the pretest was 50 and then increased to 89.67 in the first cycle test and increased again to 93.33 in the second cycle. This means the average value of all aspects from the pretest to the test cycle 1 increased by 79.34% and from cycle 1 test to cycle 2 test increased by 4.04%.